Publicznoprawna certyfikacja w obszarze kultury fizycznej jako instrument realizacji zadań publicznych – analiza na przykładzie sportów sylwetkowych - Wasilewski, Krystian (Studia Prawa Publicznego, 2026)
This article examines the correctness of the state’s performance of public tasks in the field of physical culture and sport. The point of departure is the constitutional obligation of public authorities to support the development of physical culture (Article 68(5) of the Constitution of the Republic of Poland) and its statutory implementation based on entrusting Polish sports federations with organising and running sports competitions. The analysis, carried out on the example of physique sports, demonstrates that the current regulatory model focuses almost exclusively on competitive sport. This clearly highlights the limi- tations and systemic gaps within the existing regulatory framework for executing public functions in the sports sector. The article shows that concentrating state instruments almost exclusively on competitive sports leads to the neglect of a fundamental dimension of “physical culture”, namely activities promoting the general health of the population. The lack of public-law instruments for the formal recognition of permanent physical states of individuals reveals a systemic gap in the performance of public tasks within the “physical culture” branch of governmental administration. This raises doubts as to the completeness and constitutional adequacy of the adopted regulatory solutions.